2018
DOI: 10.11607/ijp.5714
|View full text |Cite
|
Sign up to set email alerts
|

Revised, Computed Tomography–Based Lekholm and Zarb Jawbone Quality Classification

Abstract: The high reproducibility of the proposed revised CT-based Lekholm and Zarb classification obtained in the current study suggests its efficacy in distinguishing between the various combinations of compact and trabecular bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
0
14
1
3
Order By: Relevance
“… 11 , 10 These authors also reported greater losses in width than in height, but with the greatest impact in the basal part of the mandibular body. 31 , 28 In our present study, Cawood-Howell classes I and II were not represented, and patients were most frequently class IV (n = 40), followed by class III (n = 38).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“… 11 , 10 These authors also reported greater losses in width than in height, but with the greatest impact in the basal part of the mandibular body. 31 , 28 In our present study, Cawood-Howell classes I and II were not represented, and patients were most frequently class IV (n = 40), followed by class III (n = 38).…”
Section: Discussioncontrasting
confidence: 49%
“…developed a modification of the classification of the Lekholm & Zarb classification, which included five classes. 28 Since the works of Misch, computed tomography has been considered a valid and precise method of measuring cancellous and cortical bone density. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Information on patient's demographic characteristics and clinical assessments was collected after screening files and radiographs (peri‐apical film and cone‐beam CT) from patients that received dental implant restoration from March 2011 to March 2019, at the Shanghai Ninth People's Hospital. The following categorical information was collected: length of the implant (8.0 mm or 10.0 mm); diameter of the implant (3.3 mm, 4.1 mm, and 4.8 mm); implant type (Tissue level or Bone level); location of the implant (4 categories: anterior maxilla, posterior maxilla, anterior mandible, and posterior mandible); bone graft (presence or absence); periodontal disease status (classified into 3 categories: mild: 1–2 mm clinical attachment loss (CAL), moderate: 3–4 mm CAL, and severe: ≥5 mm CAL) 26 ; quality of the bone (classified into 4 categories according to CBCT: type 1: entirely homogenous compact bone, type 2: thick layer of compact bone surrounding a core of dense trabecular bone; type 3: thin layer of compact bone surrounding a core of dense trabecular bone; and type 4: thin layer of compact bone surrounding a core of low‐density trabecular bone) 27 ; and insertion torque (classified into 3 categories: <15 Ncm, 15 to 50 Ncm, and ≥50 Ncm).…”
Section: Methodsmentioning
confidence: 99%
“…The bone tissue was evaluated and categorized over the years, by different authors. [11][12][13][14][15] However, not a single classification was directly correlated to the implant therapy success. It is not possible to predict the subtle differences in bone quality when applying either the Lekholm and Zarb [11] or Misch [12] classifications, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15] However, not a single classification was directly correlated to the implant therapy success. It is not possible to predict the subtle differences in bone quality when applying either the Lekholm and Zarb [11] or Misch [12] classifications, respectively. For this reason, Trisi and Rao [13] and Norton and Gamble [14] demonstrated that subjective methods of evaluating bone quality assessment are useful only when clinically assessing up to three classes of bone quality [15].…”
Section: Resultsmentioning
confidence: 99%